PENGEMBANGAN MEDIA PEMBELAJARAN SMART APPS CREATOR BERBASIS ANDROID UNTUK MENINGKATKAN PRESTASI BELAJAR - Utami Wulandari; Bayu Insanistyo (DIADIK, 2024)
The purpose of this study is to describes: (1) Learning media with Android-based smart apps creators that are feasible to improve student learning achievements. (2) the effectiveness of learning media with Android-based Smart Apps Creator (SAC) in improving student learning achievement. This research is a type of development research (R&D). This research was developed by using the five-step ADDIE development model, that are 1) analyze, 2) design, 3) development, 4) implementation, 5) evaluation. The subjects in this study were 21 students of SD IT Insan Mulia, Bengkulu City for a limited trial and 44 students of class V SD Negeri 65 Bengkulu City for a large-scale trial. The data collection techniques in this study were interviews, observations and student test results. The data analysis used is media feasibility analysis by using expert test and then media effectiveness test using the t test. The conclusions of this research are (1) Learning media with Android-based smart apps creators developed are feasible in improving student achievement on social studies subjects in fifth grade student (2) Learning media with android-based smart apps creators developed are effective in improving student achievement on social studies subjects in fifth grade student based on the results of limited trials and broad-scale tests